Beyond “Know-Who”: The Instrumental Role of Relationship Competency among SME Entrepreneurs - Ahmad, Noor Hazlina; Halim, Hasliza Abdul (Journal of Asian Business Strategy, 2013)
This paper reports the findings of an exploratory empirical study that aims to primarily examine the instrumental role of relationship competency among SME entrepreneurs by utilising a comparative data from Australia and Malaysia. A sample of 20 SME entrepreneurs from Australia and Malaysia participated in this study. A series of interviews were conducted to probe into the behaviours that delineate relationship competency among these entrepreneurs. The results showed that SME entrepreneurs in both countries highlighted the importance of relationship (also referred to as social competency) in managing their ventures. This study provides entrepreneurs with knowledge about the way they should operate their business and encourages them to be conscious of the importance of relationship and networking in sustaining their business and increasing the odds of success. The study also demonstrates that entrepreneurs could reap a lot of benefits and at the same time overcome their limitations if they are able to equip themselves with relationship competency.